Under 5 mortality rate and its contributors in Zhejiang Province of China from 2000 to 2009 - Xu, Yan-Hua; Huang, Xin-Wen; Yang, Ru-Lai (Translational Pediatrics; Vol 2, No 1 (January 06, 2013): Translational Pediatrics, 2013)
Objective: By analyzing the under 5 mortality rate (U5MR) and its contributors in Zhejiang Province of China from 2000 to 2009, we tried to understand the trend of U5MR change in Zhejiang Province and thus propose strategies to reduce child mortality. Methods: Thirty cities/counties/districts from Zhejiang Province were selected using stratified cluster sampling approach. Children under five years in these areas were enrolled as the subjects. The U5MR and its contributors were analyzed in terms of age, migration status of mothers, and other indicators using classic descriptive methods and Chi square test. Results: The U5MR in Zhejiang Province showed a declining trend from 14.83‰ in 2000 to 9.49‰ in 2009. In 2009, the U5MR was significantly higher in the rural areas than in the urban areas (9.14‰ vs.6.50‰, P